Inicial nasal mucosa detachment using piezoelectric device in the Le Fort I osteotomy: A technical note - Shinohara, Elio Hitoshi [UNESP]; Kaba, Shajadi Carlos Pardo; Ruiz, Marcelo Martinson; Horikawa, Fernando Kendi (Wolters Kluwer, 2013)
In maxillary Le Fort I type osteotomy the detachment of the nasal mucosa should be done carefully. Piezoelectric surgery contributed much to increase the safety of osteotomies, despite the initial advantage of minimizing the risk of injury in nervous tissue, mainly in bilateral sagittal split osteotomy; we use the piezoelectric device for the initial detachment of the nasal mucosa in the maxillary osteotomy.
Keywords: Maxillary osteotomy; Orthognathic surgery; Piezosurgery